Reactive assistance or proactive protection? Social protection and climate resilience in the Sahel region - Desai, Bina; Meddings, George; Läderach, Peter R.D.; Campbell, Raramai (2023)
The Sahel region is at the forefront of climate change, with increasing temperatures and extreme weather events predicted to accelerate at a greater rate than the global average. Most of the region’s countries rank as highly vulnerable and least prepared to face climate change risks, as insecurity, rising food prices and weak national governance systems further exacerbate existing vulnerability of many communities. In this context, aligning social protection and climate change adaptation objectives may have the potential to accelerate chronic poverty reduction as well as adaptive capacities of poor households and increase climate resilience. This report is part of a study series on adaptive social protection, exploring whether and how practices on the ground are changing, if climate risks are considered in the design of social protection programmes, and whether adaptation measures are built into the support provided through existing schemes. Findings from the regional Sahel Adaptive Social Protection Programme and the national social protection system in Mauritania highlight the opportunities associated with closer alignment and the significant challenges that remain.